2008
DOI: 10.1074/jbc.m801812200
|View full text |Cite
|
Sign up to set email alerts
|

Diacylglycerol Specifically Blocks Spontaneous Integration of Membrane Proteins and Allows Detection of a Factor-assisted Integration

Abstract: We recently found that the spontaneous integration of M13 procoat is blocked by diacylglycerol (DAG) (Nishiyama, K., Ikegami, A., Moser, M., Schiltz, E., Tokuda, H., and Muller, M. (2006) J. Biol. Chem. 281, 35667-35676). Here, we demonstrate that the spontaneous integration of Pf3 coat, another membrane protein that has been thought to be integrated spontaneously into liposomes, can be blocked by DAG at physiological concentrations. Moreover, the spontaneous integration of the membrane potential-independent v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
75
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(77 citation statements)
references
References 43 publications
2
75
0
Order By: Relevance
“…However DAG addition provides a kind of 'seal' so that II Mtl insertion is entirely dependent on the SRP and SecYEG complexes (Kawashima et al, 2008). If DAG is present in sufficient amounts in native E. coli membranes, then the experiments reported by Kawashima et al (2008) of the bilayer and micellar forms of II Glc in vitro does not prove that this occurs at an appreciable rate in vivo. Interestingly, the presence of 'soluble' SecY and FtsY has been demonstrated (Ito & Akiyama, 1991;M.…”
Section: Technique Nature Of Information Obtainedmentioning
confidence: 84%
See 1 more Smart Citation
“…However DAG addition provides a kind of 'seal' so that II Mtl insertion is entirely dependent on the SRP and SecYEG complexes (Kawashima et al, 2008). If DAG is present in sufficient amounts in native E. coli membranes, then the experiments reported by Kawashima et al (2008) of the bilayer and micellar forms of II Glc in vitro does not prove that this occurs at an appreciable rate in vivo. Interestingly, the presence of 'soluble' SecY and FtsY has been demonstrated (Ito & Akiyama, 1991;M.…”
Section: Technique Nature Of Information Obtainedmentioning
confidence: 84%
“…It has been found that without the minor E. coli lipid DAG, II Mtl can insert into phospholipid vesicles in vitro via a spontaneous unassisted integration process (Nishiyama et al, 2006). However DAG addition provides a kind of 'seal' so that II Mtl insertion is entirely dependent on the SRP and SecYEG complexes (Kawashima et al, 2008). If DAG is present in sufficient amounts in native E. coli membranes, then the experiments reported by Kawashima et al (2008) of the bilayer and micellar forms of II Glc in vitro does not prove that this occurs at an appreciable rate in vivo.…”
Section: Technique Nature Of Information Obtainedmentioning
confidence: 99%
“…A dgkA mutant, deficient in DAG kinase, expresses up to ∼10% DAG (19,20). However, overproduction of dgkA did not affect the DAG expression, suggesting the occurrence of tight regulation as to DAG expression (17). Several genes are known to be involved in DAG biosynthesis, i.e., mdoB (22,23), pgpB (24)(25)(26), and eptB (27).…”
Section: Spontaneous Insertion and Diacylglycerol (Dag)mentioning
confidence: 99%
“…The existence of DAG has been shown; however, its precise function remains unclear. It is feasible that the in vivo role of DAG is to block deregulated spontaneous insertion (7,17). Wild-type E. coli cells express DAG at ∼1.5% as to phospholipids (17).…”
Section: Spontaneous Insertion and Diacylglycerol (Dag)mentioning
confidence: 99%
See 1 more Smart Citation